Hypercorrections in a Western Basque text: What do they tell us about sibilant mergers? - Krajewska, Dorota (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2025)
This paper analyses two 18th century texts and focuses on hypercorrections found in the spelling of sibilants, i.e. examples where an etymological apical fricative is represented with spelling elsewhere used for laminal fricatives. The texts used are Lubieta’s dictionary (written in the central variety of Donostia/San Sebastián) and sermons composed by Bizente Sarria (written in the western variety of Etxebarri). As for Lubieta’s text, in previous research hypercorrections have been interpreted to be related to an ongoing merger in which the apico-alveolar fricative merges with the apico-laminal, and the remaining sound is the laminal. In Sarria’s speech, however, another merger pattern was present, in which laminal and apical fricatives merge in favour of the latter. Because of that, hypercorrections found in that text are hypothesised to be purely graphical. Using quantitative methods, the paper compares the patterns found in spellings found in the two texts in order to better understand merger processes involved (and especially hypercorrections), but also to reflect on the methodology which can be used to analyse such issues.